STUDENTS’ PERCEPTION ON THE USE OF AI IN ENGLISH LANGUAGE LEARNING - Arifatin, Fais Wahidatul; Setyaningrum, Riya Risqi (Universitas PGRI Sumatera Barat, 2024)
This research paper aims to investigate students' perceptions regarding the integration of Artificial Intelligence (AI) in English language learning. With the increasing prevalence of AI technology in educational settings, understanding how students perceive its role in enhancing language acquisition is of paramount importance. This study employed a qualitative approach with narrative inquiry method, to explore students' attitudes, beliefs, and experiences related to AI integration in their English learning journey. The participants of this study were 20 students from Accounting, Management and Islamic Economic from Faculty of Economic and Business Universitas Muhammadiyah Lamongan. The findings from this research shed light on the benefits, challenges, and potential areas of improvement in utilizing AI for English language learning. The result shows that this study reflect a generally positive attitude toward the integration of AI in English language learning. Participants recognized the potential benefits of AI, such as personalized learning pathways, instant feedback, and enhanced practice opportunities. Hence, they are knowing the errors, speeding up the process and adding the insight into thinking.